IMPLEMENTASI PERUBAHAN MEDIA PEMBELAJARAN MAHASISWA BERBASIS DARING PADA MASA PANDEMI - Muh. Anwar HM; Andi Syakirah A. Bolong; Irmawati (Department of Islamic Education Management, 2022)
Implementation of Changes in Online Student Learning Media During Pandemic The Covid-19 pandemic has changed many aspects of life, one of which is Education, Transformation and Acceleration of Education which is a major challenge Government and educational institutions must also face changes in the learning media used by online-based students During the Covid-19 pandemic, almost all schools and universities in Indonesia applies online or online learning.The media used by students are Lentera, google meet, whatsapp, Zoom Meeting, youtube, and others. This research is a literature study and qualitative method conducted by interview method, learning outcomes have a positive impact on online learning, based on the conclusions of our research using the interview method, many are of the opinion this online learning can minimized and reduced the spread of covid 19 because this learning is mostly done at home, then the negative impact of lack understanding of the material presented by the lecture, and feelings that online learning is less effective because it does not understand the material and there are obstacles in terms of unstable internet connections and limited quotas. use of teaching media and platforms Education may be alternative solution in learning, for the sake of continuity of learning in each education unit.